2018
DOI: 10.1103/physrevd.98.074509
|View full text |Cite
|
Sign up to set email alerts
|

K+π+νν¯ decay amplitude from

Abstract: In Ref. [1] we have presented the results of an exploratory lattice QCD computation of the long-distance contribution to the K þ → π þ νν decay amplitude. In the present paper we describe the details of this calculation, which includes the implementation of a number of novel techniques. The K þ → π þ νν decay amplitude is dominated by short-distance contributions which can be computed in perturbation theory with the only required nonperturbative input being the relatively well-known form factors of semileptoni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 51 publications
0
39
0
Order By: Relevance
“…(61) as in Refs. [201,200], it is clear that the correlation function has the asymptotic time dependence Figure 11: Contractions for the π − → π + e − e − transition in Eqs. (62) and (63).…”
Section: 21mentioning
confidence: 99%
“…(61) as in Refs. [201,200], it is clear that the correlation function has the asymptotic time dependence Figure 11: Contractions for the π − → π + e − e − transition in Eqs. (62) and (63).…”
Section: 21mentioning
confidence: 99%
“…Since the LD contributions to K L → π 0 νν decays are negligible, we do not discuss these decays further in this paper. This paper is the latest in a series of lattice QCD studies of the rare kaon decays K → π + − and K → πνν, in which we have developed the theoretical framework and performed exploratory numerical calculations [13][14][15][16][17][18][19][20][21][22][23][24]. Here we focus on the LD contributions to the K + → π + νν decay amplitude.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, we computed the amplitude in Refs. [23,24] at a single choice of momenta. The momentum dependence of the decay amplitude was therefore unresolved and is the focus of the study reported here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With lattice QCD simulations having reached an impressive level of precision for tree-level parameters of the electroweak interaction, it becomes timely and important to study higher-order electroweak corrections. The examples of such lattice applications include the QED corrections to hadron masses [8][9][10][11][12][13][14][15] and leptonic decay rates [16][17][18][19] and a series of higher-order electroweak effects, such as K L -K S mass difference [20][21][22], K [23], rare kaon decays [24][25][26][27][28][29] and double beta decays [30][31][32][33][34][35]. As for the γW -box contribution, which is a QED correction to semileptonic decays, it still remains a new horizon for lattice QCD.…”
mentioning
confidence: 99%